The Influence of Prenatal Classes on Anxiety in Primigravida Mothers - Astri Ulina Saragih; Yessy Arisman; Ulfa Khomania Aulia; Risky Yulanda (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Psychological conditions such as anxiety in pregnant women can have a significant impact on the health of the mother and fetus. One of the methods that can be used to minimize this level of anxiety is by providing education through Prenatal class activities. This study aims to evaluate the effect of participation in Prenatal classes on the level of anxiety in mothers with their first pregnancy. The method used in this study is quantitative with a quasi-experimental design using a non-equivalent control group design. The population in this study included all mothers with their first pregnancy in the Lubuk Pakam Health Center working area, totaling 46 people, with a sample size of 30 people selected by purposive sampling. Data analysis was carried out using the Wilcoxon test with a significance level of 0.05. The test results stated that in the experimental group the p-value was 0.000, while in the control group it was 0.041. Based on these results, it can be concluded that involvement in the pregnant mother class has an impact on reducing the level of anxiety in mothers with their first pregnancy in the area.